The Influence of Product Quality and Prices on Customer Loyalty at Halal Mart Cibubur - Purnama, Ayu; Kumala, Destiana; Utarindasari, Destiana (International Journal of Sharia Business Management, 2023)
This research was conducted with the aim of knowing: 1) The effect of product quality on customer loyalty at the halal mart in Permata Cibubur. 2) To determine the effect of price on customer loyalty at halal mart in Permata Cibubur. The method used is quantitative with sampling in this study as many as 75 respondents with a purposive sampling technique. Data analysis techniques in this study used multiple linear regression analysis with partial regression test (t-test) and simultaneous test (F). The calculation process is assisted by the IBM SPSS 22 software application program. The test results show that there is a significant influence between product quality and customer loyalty at the Halal Mart in Permata Cibubur. There is a significant influence between price and customer loyalty at the Halal Mart in Permata Cibubur. There is a significant effect of product quality and price on customer loyalty at the Halal Mart in Permata Cibubur